Maturity-Onset Diabetes of the Young Identified Among Algerian Probands with Early-Onset Diabetes - Bouldjennet F; Gjesing AP; Azzouz M; Abderrahman SA; Guecier AE; Ali S; Oudjit B; Mennadi-Lacete F; Yargui L; Boudiba A; Chibane A; Touil-Boukoffa C; et al. (Diabetes, Metabolic Syndrome and Obesity, 2020)
Faiza Bouldjennet,1,* Anette P Gjesing,2,* Malha Azzouz,3 Samir Ait Abderrahman,4 Amina El Guecier,5 Said Ali,6 Brahim Oudjit,4 Farida Mennadi-Lacete,7 Lyèce Yargui,6 Aissa Boudiba,3 Ahcène Chibane,5 Chafia Touil-Boukoffa,1 Torben Hansen,2 Rachida Raache1 1Laboratory of Cellular and Molecular Biology, Cytokine and NO Synthase Team, University of Science and Technology, Houari Boumediene (USTHB), Algiers, Algeria; 2The Novo Nordisk Foundation Center for Basic Metabolic Research, Faculty of Health Sciences, University of Copenhagen, Copenhagen, Denmark; 3Diabetology Department of Mustapha Pacha Hospital, Algiers, Algeria; 4Diabetology Department of Mohamed Seghir Nekkache Hospital, Algiers, Algeria; 5Internal Medicine Department of Djillali Bounaâma Hospital, Algiers, Algeria; 6Laboratory of Biochemistry, Mustapha Pacha, Algiers, Algeria; 7Pediatric Department of Parnet Hospital, Algiers, Algeria*These authors contributed equally to this workCorrespondence: Anette P Gjesing; Rachida Raache Email anette.gjesing@sund.ku.dk; raache_ipa@yahoo.frAim: To investigate the prevalence of variants within selected maturity-onset diabetes of the young (MODY)-genes among Algerian patients initially diagnosed with type 1 diabetes (T1D) or type 2 diabetes (T2D), yet presenting with a MODY-like phenotype.Methods: Eight unrelated patients with early-onset diabetes (before 30 years) and six relatives with diabetes were examined by targeted re-sequencing for variants in genes known to be involved in MODY (HNF1A, GCK, HNF4A, HNF1B, INS, ABCC8, KCNJ1). Clinical data for probands were retrieved from hospital records.Results: A total of 12 variants were identified, of which three were classified as pathogenic and one as a variant of uncertain clinical significance (VUS). Two of the pathogenic variants were found in GCK (p.Gly261Arg and p.Met210Lys, respectively) in one proband each and the remaining pathogenic variant was found in HNF1B (p.Gly76Cys) in a proband also carrying the VUS in HNF1A (p.Thr156Met).Conclusion: Variants in known MODY-genes can be the cause of early-onset diabetes in Algerians diagnosed with T1D or T2D among patients presenting with a MODY-like phenotype; thus, genetic screening should be considered.Keywords: MODY, type 1 diabetes, early-onset, monogenic diabetes, genes